The Conversational Implicature in the Movie Script of Freedom Writers - Nia Septiyanti; Bibit Suhatmady; Yuni Utami Asih (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2020)
This study aims at analyzing the flouting conversational maxims, types of generalized and particularized conversational implicature and its implied meanings. It belongs to a qualitative content analysis approach. The data source comes from the movie script of Freedom Writers in the form of conversation and utterances of the characters that are appropriate with the focused analysis. It uses the Grice’s theory of flouting maxims as well as implicature and Searle’s theory of illocutionary acts to support the data analysis. It reveals that the characters flouted the maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner that create the presence of implicature. They used generalized conversational implicature and particularized conversational implicature to calculate the implied meanings. It found that the implied meanings are intended to give information, to deny truthful information, to do action, to express feeling, and to show politeness and respect